2012
DOI: 10.1590/s0100-736x2012000800017
|View full text |Cite
|
Sign up to set email alerts
|

Determinação de hemogregarina em Boa constrictor constrictor mantidos em cativeiro

Abstract: O presente estudo teve como objetivo determinar a presença de hemogregarina em boídeos mantidos em cativeiro no Estado do Pará, bem como, relacionar a hemoparasitose com pre-disposição sexual, alterações clínicas e hematológicas e a presença de ectoparasitos. Esta pesquisa teve autorização do Sistema de Autorização e Informação em Biodiversidade do Instituto Brasileiro do Meio Ambiente e dos Recursos Naturais Renováveis para ser realizado. Utilizaram-se 19 serpentes da família Boidae mantidas em cativeiro, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…This was the first study conducted in the state of Pará to observe the presence of hemoparasites in I. Iguana and correlate the findings with hematological values. Hemoparasite infection levels in the animals of the present study were similar to those found in Belém, Pará, by Luz et al (2012) in Boa constrictor constrictor snakes, who found haemogregarines in 47.37% of the animals (77.78% male and 22.22% female). These authors also did not observe statistical differences between genders.…”
Section: Discussionsupporting
confidence: 90%
“…This was the first study conducted in the state of Pará to observe the presence of hemoparasites in I. Iguana and correlate the findings with hematological values. Hemoparasite infection levels in the animals of the present study were similar to those found in Belém, Pará, by Luz et al (2012) in Boa constrictor constrictor snakes, who found haemogregarines in 47.37% of the animals (77.78% male and 22.22% female). These authors also did not observe statistical differences between genders.…”
Section: Discussionsupporting
confidence: 90%
“…Its prevalence can be explained based on its transmission, which involves 1 arthropod as vector (ticks, mites, mosquitoes, etc.). Intraerythrocytic hepatozoonosis is considered asymptomatic; however, it can cause hemolytic anemia (subclinical infections), immunosuppression and predisposition to secondary infections (Lopes et al, 2010;Luz et al, 2012). In Brazil, the prevalence of infection ranged 16.4-38.9% in captive B. constrictor, but may be in latent period with low percentages of parasitemia (0.15-0.52%).…”
Section: Discussionmentioning
confidence: 99%